2013
DOI: 10.1089/cell.2012.0037
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Supports Reprogramming of Mesenchymal Stromal Cells Via Induction of Embryonic Stem Cell–Specific microRNA-302 Cluster and Pluripotency-Associated Genes

Abstract: Pluripotency is characterized by specific transcription factors such as OCT4, NANOG, and SOX2, but also by pluripotency-associated microRNAs (miRs). Somatic cells can be reprogrammed by forced expression of these factors leading to induced pluripotent stem cells (iPSCs) with characteristics similar to embryonic stem cells (ESCs). However, current reprogramming strategies are commonly based on viral delivery of the pluripotency-associated factors, which affects the integrity of the genome and impedes the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The binding of the seed sequence in miRs to a complementary sequence in the mRNA 3′UTR promotes mRNA degradation, whereas failure to bind due to the sequences not being complementary can result in translation inhibition [21]. miR-302 transcriptionally regulates gene expression and methylation [22] and supports reprogramming in stem cells during hypoxia [23, 24]. As a putative upstream regulator of Mcl-1 expression, the role of miR-302 in protecting cardiomyocytes from H/R remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of the seed sequence in miRs to a complementary sequence in the mRNA 3′UTR promotes mRNA degradation, whereas failure to bind due to the sequences not being complementary can result in translation inhibition [21]. miR-302 transcriptionally regulates gene expression and methylation [22] and supports reprogramming in stem cells during hypoxia [23, 24]. As a putative upstream regulator of Mcl-1 expression, the role of miR-302 in protecting cardiomyocytes from H/R remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that hypoxia could improve reprogramming of cells. Foja et al [ 46 ] showed that hypoxia improved the reprogramming of MSCs into induced pluripotent stem cells (iPSCs). Adipose stem cells were also stimulated for reprogramming to iPSCs by hypoxia [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia, which stimulates glycolysis, has been reported to induce a human ESC‐like transcriptional signature in several cancer cell lines, upregulating NANOG, OCT4, SOX2, KLF4, c‐MYC, and the miR‐302 cluster . It was also shown to activate the miR‐302 cluster and other pluripotency TFs during iPSC production . These findings explain, at least partially, why iPSC generation is enhanced under hypoxic conditions .…”
Section: Induced Pluripotencymentioning
confidence: 87%